EMDR therapy for PTSD symptoms in patients with mild intellectual disability or borderline intellectual functioning and comorbid psychotic disorder: A case series. (October 2021) - Penninx Quevedo, Rosita; de Jongh, Ad; Bouwmeester, Samantha; Didden, Robert
Highlights: First study to investigate EMDR therapy for PTSD in patients with MID-BIF and a comorbid psychotic disorder. EMDR therapy is a safe, feasible and effective treatment for PTSD in patients with triple mental health problems. Treating PTSD in MID-BIF improves psychiatric symptomatology as well as general well-being. Abstract: Background: Little is known about the effectiveness of EMDR therapy for PTSD symptoms in persons with mild intellectual disability or borderline intellectual functioning (MID-BIF, IQ 50–85) and psychosis. Aims: To examine effectiveness, feasibility, and safety of eye movement desensitization and reprocessing (EMDR) therapy in six patients with MID-BIF, PTSD and psychotic disorder. Methods and procedures: Data were collected in a multiple baseline across-subjects design. Before, during and after treatment, weekly assessments on PTSD symptoms and adverse events were carried out. PTSD classification was assessed, and severity of hallucinations, delusions, and general psychopathology were measured at pretreatment, posttreatment and three-month follow-up. Outcomes and results: There were no dropouts and five of the six participants completed treatment early. They showed a decrease in PTSD symptom severity and did no longer meet DSM-5 PTSD criteria at posttreatment. Results were maintained at follow-up. Symptoms did not exacerbate as indicated by a significant decrease in general psychopathology (in five participants) and an improvement in general functioning. In five participants severity of psychotic symptoms decreased. Conclusions and implications: EMDR therapy is safe and feasible and the results suggest that it can be an effective treatment for PTSD in patients with triple mental health problems in a tertiary mental health treatment setting.